2015
DOI: 10.1080/01488376.2014.994798
|View full text |Cite
|
Sign up to set email alerts
|

Families’ Satisfaction With Public Housing in Saudi Arabia and Its Effect on the Quality of Their Lives

Abstract: This study examined the impact of participating in social services programs designed for families who reside in supportive housing on their overall quality of life. A random sample of 300 households from a total of 1,400 families who reside in the Prince Salman Housing Program (PSHP) in Saudi Arabia were selected. PSHP provides a number of services such as job training, education, and micro-credit training. The following 6 independent variables were examined using 1 dependent variable, "quality of life": chall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 34 publications
0
2
0
3
Order By: Relevance
“…However, over time, from the 5th Plan, the trend became relaxed leading to the housing shortage. Soliman et al (2015) investigated the impact of participating in social services programmes designed for families who reside in supportive homes on their overall quality of life using families who reside in the Prince Salman Housing Programme in Saudi Arabia.…”
Section: Housing Financementioning
confidence: 99%
“…However, over time, from the 5th Plan, the trend became relaxed leading to the housing shortage. Soliman et al (2015) investigated the impact of participating in social services programmes designed for families who reside in supportive homes on their overall quality of life using families who reside in the Prince Salman Housing Programme in Saudi Arabia.…”
Section: Housing Financementioning
confidence: 99%
“…In addition, some studies have reported that the male subjects have obtained higher Quality of Life scores compared to their female counterparts (Khaje-Bishak et al 2014). A study in Saudi Arabia indicated a significant difference between the total mean score of life quality among elderly men and women (Soliman et al 2015). A study in Vietnam assessed the total life quality scores among the elderly men (75.32) and women (72.32) and reported that the life quality among the el- derly men in all dimensions was higher than that of the women (Van Nguyen et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Çeşitli ihtiyaçlar, zorluklar ve engeller nedeniyle aileler yaşam kalitelerini etkileyen koşullarla karşılaşabilmektedir [13]. Kişilerin daha iyi yaşam standardına kavuşturulması ve refah düzeyinin arttırılması gerekliliğinin, 2.…”
Section: Yaşam Kali̇tesi̇ Kavramiunclassified
“…Diğer yandan, yapılan araştırmalarda yaşam kalitesi, farklı amaç ve hedefler doğrultusunda, farklı yöntemlerle ölçülmekte ve araştırma ölçekleri de bu doğrultuda birbirinden farklılık göstermektedir [17][18][19][20][21][22]. Yaşam kalitesinin ölçülmesinde kullanılacak göstergelerin türü ve kriterleri konusunda da uzlaşma bulunmamaktadır [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Yaşam kalitesi ile ilgili faktörler kentlere, kültürlere, şartlara göre ve zaman içinde değişebilmektedir [11].…”
Section: Yaşam Kali̇tesi̇ Kavramiunclassified
See 1 more Smart Citation